Gangguan Emosional Anak Akibat Tayangan Misteri Televisi (Studi Kasus Pada Anak Usia 2-11 Tahun) - Musfira, Musfira (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2018)
This study aims to: (1) understand the emotional disturbance experienced by children aged 2-10 years old because they often watch a mystery program an television, (2) understand the physical problems experienced by children aged 2-10 years old as a result of emotional disturbance because the frequently watch mystery television program.This research is a qualitative research with case study method with three children with different age classifications as research subject. Two children are from pre-operational phase and a child from the concrete operational phase. The data collection techniques used in this research are observation, interview and documentation.The results provide conclusion that the emotional distress experienced by children (2-10 years old) is whyny, often delirious, coward and always felt overshadowed, not independent, and fear of certain animals and thus affects his physical with the chest thumping, trembling and cold sweat and stamina of his body became weak, so vulnerable to disease. Emotional disturbances experienced by each child depend on the intensity of children watching mystery program in the mystique level contained in those program